Gum Arabic Reduces C-Reactive Protein in Chronic Kidney Disease Patients without Affecting Urea or Indoxyl Sulfate Levels - Sarra Elamin; Mariam J. Alkhawaja; Amina Y. Bukhamsin; Mohamed A. S. Idris; Muntasir M. Abdelrahman; Nasrulla K. Abutaleb; Abdulrahman A. Housawi (International Journal of Nephrology)
Introduction. Gum Arabic (GA) is a complex polysaccharide with proven prebiotic properties and potentially beneficial systemic effects. Methods. We randomly allocated 36 chronic kidney disease (CKD) patients to receive 10, 20, or 40 grams daily of GA for four weeks and studied the systemic effects of this intervention. Results. Thirty participants completed the study with baseline glomerular filtration rate 29.1±9.9 mL/min/1.7 m2. In contrast to previous observations, we found no effect on serum urea or creatinine levels. GA supplementation was associated with a small but statistically significant drop in serum sodium level (138±2 to 136±3 mmol/L, p = 0.002) without affecting other electrolytes, urine volume, or indoxyl sulfate (IS) levels. GA supplementation was also associated with a significant drop in C-reactive protein (CRP) level (3.5±1.5 to 2.8±1.6 ng/mL, p = 0.02) even in patients who received only 10 g/day (4.4±1.2 to 3.2±1.5 ng/mL, p = 0.03). Conclusions. Supplementing the diet of CKD patients with 10–40 g/day of GA significantly reduced CRP level which could have a positive impact on these patients’ morbidity and mortality. This trial is registered with Saudi Clinical Trial Registry number 15011402.